Selective uterine artery embolization is a valid adjuvant treatment of choriocarcinoma: a case report and literature review - Chen, Yuying; Sun, Tingting; Yuan, Linjing; Huang, Yucong; Yusufu, Aligu; Zhang, Yang; Zhang, Xiaoyan; He, Shasha; Ren, Yufeng; Yao, Shuzhong; Yang, Guofen (Frontiers in Oncology, 2024)
BackgroundCervical choriocarcinoma is an extremely rare malignancy that is often misdiagnosed due to its nonspecific symptoms, such as vaginal bleeding.Case reportA 39-year-old female presented to the emergency department of the First Affiliated Hospital of Sun Yat-sen University with vaginal bleeding and a serum β-human chorionic gonadotropin (β-HCG) level of 229,386 mIU/mL. Initially, she was misdiagnosed with cervical pregnancy and subsequently underwent selective uterine artery embolization and cervical mass excision. However, pathological examination revealed the diagnosis of cervical choriocarcinoma.ConclusionThis case highlights the propensity for misdiagnosis of cervical choriocarcinoma. Selective uterine artery embolization proves to be an efficient measure to manage hemorrhage and potentially avoid unnecessary hysterectomy.